Over and over and out [emergency radio systems]. - Riezenman, M.J (IEEE spectrum)
In the future, emergency systems will have to account for the orderly use of multiple communications channels. This is most easily done using digital radios. Although much has been said about such radios in connection with the communications problems on 9/11, the fact is that the Fire Department of the City of New York (FDNY) had no such radios on the scene that day. Redundancy, clearly, was not overlooked by the FDNY. What the department did not anticipate was the scope and scale of the disaster. Future systems will doubtless have even more redundancy, some of it deployed well out of the immediate hazard area. Emergency repeaters mounted on helicopters might also prove valuable in dealing with skyscraper fires, especially since they could easily change position as needed to ensure coverage of a particular area.